IDENTIFIKASI KERAGAMAN MORFOLOGI DAUN TANAMAN UBI KAYU (Manihot escolenta Cantz) BERDASARKAN PENANDA RAPD (RANDOM AMPLIFIED POLYMORPHIC DNA) - Hafiza Hazmi; Zahratul Idami; Kartika Manalu (Universitas Cokroaminoto Palopo, 2026)
Cassava Plants (Manihot esculenta Crantz), traditionally cultivated and offering many benefits as food ingredients, animal feed, and industrial raw materials. Cassava is also known to be rich in carbohydrates, soluble dietary fiber, and beneficial micronutrients for the body. Morphological and genetic diversity in cassava plants is crucial for the development of superior and improved varieties. This study aims to identify the morphological diversity of cassava leaf plants (Manihot esculenta Crantz) and analyze dendrogram relationships using RAPD (Random Amplified Polymorphic DNA) markers. The research was conducted in Serdang Bedagai Regency and the laboratory of the State Islamic University of North Sumatra, Medan. The methods used included sample collection, DNA isolation, PCR amplification, electrophoresis, and data analysis. The results showed variations in leaf morphology as observed in the number of leaflets, color, and shape of leaves in cassava varieties Genderuwo, Roti, Keriting, and Jari. Morphologically, the Genderuwo and Roti cassava leaves were the most similar. The dendrogram analysis using RAPD primers OPA 2, OPA 3, OPA 5, and OPA 7 showed a close relationship between Genderuwo and Roti varieties (coefficient 0.85), while the Jari variety had the most distant relationship (coefficient 0.60). This research can serve as a reference in cassava plant breeding to produce superior varieties